Akibat Hukum Wanprestasi Yang Dilakukan Nasabah Terhadap Koperasi Simpan Pinjam Dalam Perjanjian Tidak Tertulis - Yuriz Wibowo; Gunawan Djajaputra (LPPM Universitas Ekasakti Padang, 2024)
In unwritten agreements between customers and savings and loan cooperatives, defaults by customers can have significant legal consequences for both parties. Default occurs when customers do not fulfill their obligations in accordance with the agreed agreement, such as not paying installments on time. The legal consequences of this default may vary depending on the provisions contained in the agreement and the applicable law. The research method used is normative law. The results showed that for customers, the legal consequences of default can be in the form of fines or surcharges, cancellation of the agreement, or even lawsuits. Meanwhile, for savings and loan cooperatives, the legal consequences can include financial losses due to not receiving payments on time and a tainted reputation in the industry. The importance of clarity and certainty in agreements is an important emphasis in this context, so that the rights and obligations of both parties can be clearly understood. In addition, compliance with applicable laws and regulations is also a key factor in responding to defaults, so that both parties can maintain balance and fairness in their contractual relationship.